Synthetic gauge fields in synthetic dimensions: interactions and chiral edge modes. (11th March 2016) - Barbarino, Simone; Taddia, Luca; Rossini, Davide; Mazza, Leonardo; Fazio, Rosario
Abstract: Synthetic ladders realized with one-dimensional alkaline-earth(-like) fermionic gases and subject to a gauge field represent a promising environment for the investigation of quantum Hall physics with ultracold atoms. Using density-matrix renormalization group calculations, we study how the quantum Hall-like chiral edge currents are affected by repulsive atom–atom interactions. We relate the properties of such currents to the asymmetry of the spin resolved momentum distribution function, a quantity which is easily addressable in state-of-art experiments. We show that repulsive interactions significantly enhance the chiral currents. Our numerical simulations are performed for atoms with two and three internal spin states.